Production of Cellulose Microfibrils by Rhizobium - Napoli, Carolyn (1975)
Electron microscope examination of Rhizobium spp. revealed microfibrils produced by flocculating strains but not by nonflocculating strains. The microfibrils from R. trifolii (NA30) were isolated and identified as cellulose by enzymatic, X-ray diffraction, and infrared spectral analyses. Both infective and noninfective strains of R. trifolii flocculated and produced microfibrils. More infection threads were observed in clover root hairs growing in the presence of flocs in comparison with root hairs where single bacterial cells predominated.